2019
DOI: 10.31557/apjcp.2019.20.4.1199
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds in the Ethanol Extract of Marine Sponge Stylissa carteri Demonstrates Potential Anti-Cancer Activity in Breast Cancer Cells

Abstract: Objective: Despite advanced treatment options available, drug resistance develops in breast cancer (BC) patients requiring novel effective drugs. Stylissa carteri, a marine sponge predominantly living in Indonesia territories, has not been extensively studied as anti-cancer. Therefore, this study targeted to assess the anti-tumor activity of the ethanol extract of S. carteri in BC cells. Methods: S. carteri was collected from Pramuka Island, at Kepulauan Seribu National Park, Jakarta, Indonesia and extracted u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Previous studies showed that ethanol extraction of this sponge caused inhibition of proliferation and migration. 22 The IC 50 of the ethanol extract of Stylissa carteri in HCC-1954 cells was 14 μg/ml. 22 In our study, the IC 50 of the ethyl acetate fraction of Stylissa carteri was 9.25 μg/ml.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies showed that ethanol extraction of this sponge caused inhibition of proliferation and migration. 22 The IC 50 of the ethanol extract of Stylissa carteri in HCC-1954 cells was 14 μg/ml. 22 In our study, the IC 50 of the ethyl acetate fraction of Stylissa carteri was 9.25 μg/ml.…”
Section: Discussionmentioning
confidence: 98%
“…19,20 The ethanol extract of Stylissa carteri has cytotoxic effects on several cancer cell lines, including luminal A, HER2 + and triple-negative type breast cancer cells, and cervical cancer cells. 21,22 To further purify compounds of Stylissa carteri and to obtain stronger potential of anticancer fraction, this study was conducted to explore effects on fraction levels, especially on the ethyl acetate fraction. This study aimed to determine the cytotoxic effects of ethyl acetate fraction of the Stylissa carteri on trastuzumabresistance HER2+ breast cancer cells, HCC-1954 in vitro through its cytotoxicity parameters using the 3-[4,5-dimethylthiazol-2-yl] -2.5 diphenyl tetrazolium bromide (MTT) assay and estimation of 50% inhibitory concentration (IC 50 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was indicated by the decreasing diameter and increasing density of spheroids during 96 h of incubation. Spheroids were ready to use after being incubated for 96 h in accordance to the previous study (Bashari et al 2019). The spheroids are ready to use when there is a decrease in diameter, but the size of the spheroids is relatively the same.…”
Section: Discussionmentioning
confidence: 99%
“…HCC 1954 breast cancer cell line, given by Dr. med. Muhammad Hasan Bashari, M.D., M.Kes., Universitas Padjadjaran, Indonesia, was grown in the RPMI (Gibco) medium supplemented with 10% v/v FBS (Sigma) and 1% v/v penicillinstreptomycin (Gibco) (Bashari et al 2019). The cells were incubated in an incubator with 5% CO 2 at 37 o C. At 80% confluence, cells were harvested by using 0.025% trypsinEDTA (Gibco).…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation